2022
DOI: 10.3390/agronomy12040816
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Rice and Weeds and Their Nutrient Partitioning under Various Establishment Methods and Weed Management Practices in Temperate Environment

Abstract: A research trial was conducted at Agronomy Farm (SKUAST-K, Wadura, Jammu & Kashmir), during kharif 2017 and 2018 to evaluate nutrient removal in rice under various rice establishment methods and weed control measures. The study comprised of two factors: rice establishment techniques {(Transplanting (TPR); Direct seeding (DSR) and System of rice intensification (SRI)} as main plot treatments and weed control measures {(Butachlor @ 1500 g a.i ha−1 (B); Penoxsulam @ 22.5 g a.i ha−1 (P); Pyrazosulfuron ethyl +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…The congenial growth conditions prevailed because AWD under SRI method allowed the rice plant to have a greater number of phyllochrons, increased number of tillers, and highly developed roots, before the flowering phase ( Deb, 2020 ) and produced highest grain yield over all the rice production techniques evaluated. Our findings were in accordance with the findings of Chapagain and Yamaji (2010) ; Mishra and Salokhe (2011) , and Nazir et al. (2022) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The congenial growth conditions prevailed because AWD under SRI method allowed the rice plant to have a greater number of phyllochrons, increased number of tillers, and highly developed roots, before the flowering phase ( Deb, 2020 ) and produced highest grain yield over all the rice production techniques evaluated. Our findings were in accordance with the findings of Chapagain and Yamaji (2010) ; Mishra and Salokhe (2011) , and Nazir et al. (2022) .…”
Section: Discussionsupporting
confidence: 93%
“…Yield Emission Climate smartness index (CSI) during both the season under different rice production techniques in rice crop. Nazir et al (2022). Talla and Jena (2014) and Kumar et al (2016) have also reported approximately 7%-30% higher grain yield in SRI-AWD over the conventional method.…”
Section: Parametersmentioning
confidence: 95%
“…The diminishing of targeted weeds dry biomass could be connected to length of seedling as affected by chemicals allelopathic nature present in bermudagrass and sorghum extracts and powders. Water and nutrients uptake is suppressed by allelopathic chemicals thus, reducing photosynthesis and biomass growth (Nazir et al, 2022). It is envisaged from the results that effects of allelopathic action of bermudagrass and sorghum were specific to forms and plant parts.…”
Section: Shoot Length (Cm)mentioning
confidence: 99%
“…Rice production is the backbone in agricultural sector of sub-tropical and tropical countries, including Pakistan (Nazir et al, 2022). One of the major threats to sustainable crop production is infestation of weeds in crop field (Uno et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…) GR as pre-emergence fb hand weeding at 40 DAT (T 4 ) were also on par with hand weeding twice. Nazir et al [9] also evaluated Butachlor @ 1500 g a.i ha -1…”
Section: Weed Dry Weightmentioning
confidence: 99%